Vitamin D levels in early and middle pregnancy and preeclampsia: a systematic review and meta-analysis - Zakerinasab, Faezeh; Behfar, Qumars; Daghistani, Hussam; Ansari, Arina; Zadeh, Reza Hossein; Zadeh, Rasoul Hossein; Amirbeik, Amirhesam (Frontiers in Medicine, 2025)
Background and aimsPrevious studies have indicated a potential association between low vitamin D levels in early pregnancy and an increased risk of hypertensive disorders, including preeclampsia. Given the substantial maternal and fetal morbidity associated with preeclampsia, identifying preventive strategies is crucial. This meta-analysis aimed to evaluate the relationship between vitamin D status in early and middle pregnancy and the development of preeclampsia.MethodsA comprehensive literature search of PubMed, Scopus, Web of Science, and Cochrane Library databases was conducted up to June 23, 2023, to identify relevant observational studies. Included studies were assessed for methodological quality, and data on maternal vitamin D concentration and the risk of preeclampsia were extracted.ResultsTwenty-nine observational studies with 74,061 participants were included. Women with preeclampsia had significantly lower vitamin D levels than those without (SMD −0.28, 95% CI −0.39 to −0.17, p < 0.001). Although lower vitamin D levels showed a trend toward higher preeclampsia risk, pooled odds ratios for insufficiency (OR 1.05, 95% CI 0.78–1.42) and deficiency (OR 1.25, 95% CI 0.89–1.76) were not statistically significant. Subgroup analyses suggested a possible dose–response relationship, especially when vitamin D was measured in early or mid-pregnancy. Additional analyses by assay method, cut-off definitions, region, and study design also supported an association between lower vitamin D and preeclampsia risk.ConclusionThe findings of this meta-analysis suggest a potential association between low maternal vitamin D levels and an increased risk of preeclampsia, particularly when measured prior to the late pregnancy. However, the precise timing of this association requires further investigation. To definitively establish the role of vitamin D supplementation in preventing preeclampsia, well-designed randomized controlled trials are needed to determine optimal dosage and timing of intervention, as well as to assess cost-effectiveness.Systematic review registrationRegistered in OSF: https://osf.io/qwh6a (Unique ID: qwh6a).